PENGARUH INDUSTRI BATU BATA TERHADAP PENINGKATAN PENDAPATAN MASYARAKAT DI DESA RAMBAHAN KECAMATAN MUARA BULIAN - Alfazri Rahmadani,; Wina Sari Asmara,; M. Andriansyah,; Raden Hebat, (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
This research is quantitative research with a survey approach. The research population is people who work in the brick industry in Rambahan Village. The research sample uses a saturated sample where all members of the population are sampled, namely 60 people. The research results show that, partially, the brick industry has a significant effect on increasing people's income by 48.6%. Simultaneously there is a significant influence between the brick industry on increasing people's income by 17.5%, with the obtained value of fcount>ftable (12.311>3.16). This shows reject H0 and accept Ha. This means that there is a significant influence between the brick industry together (simultaneously) on increasing people's income in Rambahan Village. Where if the brick industry gets better, the increase in people's income in Rambahan Village will also be better. Meanwhile, the remaining 82.5% was influenced by other variables not included in this research